2009
DOI: 10.1021/ja807935y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Kinetic Macrocyclization

Abstract: In this article, the highly efficient formation of a series of recently discovered aromatic oligoamide macrocycles consisting of six meta-linked residues is first discussed. The macrocycles, with their backbones rigidified by three-center hydrogen bonds, were found to form in high yields that deviate dramatically from the theoretically allowed value obtained from kinetic simulation of a typical kinetically controlled macrocyclization reaction. The folding of the uncyclized six-residue oligomeric precursors, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 37 publications
1
94
0
1
Order By: Relevance
“…This is usually the most critical step for obtaining an efficient macrocyclization. Entropic and enthalpic factors play an important role in the preparation of macrocyclic structures [9][10][11]. To favour the macrocyclization over the competing oligomerization/polymerization reactions, the open-chain precursor must be preorganized in a folded conformation, therefore approaching both [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…This is usually the most critical step for obtaining an efficient macrocyclization. Entropic and enthalpic factors play an important role in the preparation of macrocyclic structures [9][10][11]. To favour the macrocyclization over the competing oligomerization/polymerization reactions, the open-chain precursor must be preorganized in a folded conformation, therefore approaching both [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Such structures display a wide range of unusual electronic properties, not seen in linear analogues 3, 4. The inherent difficulty of synthesizing such molecules is often due to the competition between cyclization and polymerization 5.…”
mentioning
confidence: 99%
“…[49] When benzene-1,4-dicarboxylic acid precursors were introduced, the cavities of the macrocycles could be enlarged remarkably. [47] Li and Yuan et al also utilized a similar strategy to prepare a number of aromatic amide macrocycles from different diamines and diacyl chlorides, [50,51] while Huc and Jiang et al reported the synthesis of several aromatic amide macrocycles through the self-coupling of discrete quinoline amino acids. [52,53] Zeng and co-workers systematically studied the selfcoupling of several meta-substituted amino acids under different reaction conditions.…”
Section: Promotion Of Covalent and Noncovalent Macrocyclizationmentioning
confidence: 99%